2021
DOI: 10.1002/er.7330
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of sulfur‐doped porous carbon for supercapacitor and gas adsorption applications

Abstract: Heteroatom-doped porous carbon materials have great potential for both capacitive energy storage and gas sorption applications. This article reports the synthesis of highly porous sulfur-doped carbon from thiophene using an in situ self-doping strategy followed by KOH activation. A series of highly porous sulfur-containing carbon materials with high surface area and pore volume were prepared through variation of activation temperature from 600 C to 900 C and applied as supercapacitor electrodes in alkaline as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…CC and C–C bonding were seen in the C 1s XPS spectra at 284.1 and 285.0 eV, respectively, while C–S and CO bonding were verified at the higher binding energy levels with peak positions of 286 and 288 eV . The S 2p spectrum was separated into three peaks: two major peaks located at 163.37 and 164.64 eV correspond to S 2p 3/2 and S 2p 1/2 peaks of the covalent C–S bond of thiophene-type sulfur because of the spin–orbit coupling, and a broad peak located at 167.8 eV is assigned to the C-(SOx)-C bond. , Additionally, using CHNS analysis, it was shown that the proportion (weight %) of S in the carbon framework reduced from 9.6 for CS-1000 to 5.5 for CS-1100 and 3.25 for CS-1200, respectively. The elimination of sulfur-containing groups via high-temperature annealing is what caused the percentage fall in the sulfur concentration .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…CC and C–C bonding were seen in the C 1s XPS spectra at 284.1 and 285.0 eV, respectively, while C–S and CO bonding were verified at the higher binding energy levels with peak positions of 286 and 288 eV . The S 2p spectrum was separated into three peaks: two major peaks located at 163.37 and 164.64 eV correspond to S 2p 3/2 and S 2p 1/2 peaks of the covalent C–S bond of thiophene-type sulfur because of the spin–orbit coupling, and a broad peak located at 167.8 eV is assigned to the C-(SOx)-C bond. , Additionally, using CHNS analysis, it was shown that the proportion (weight %) of S in the carbon framework reduced from 9.6 for CS-1000 to 5.5 for CS-1100 and 3.25 for CS-1200, respectively. The elimination of sulfur-containing groups via high-temperature annealing is what caused the percentage fall in the sulfur concentration .…”
Section: Resultsmentioning
confidence: 97%
“…A broad peak centered at roughly 2θ = 24.9° corresponds to (200) graphite planes, whereas another peak centered at roughly 2θ of 43.5° corresponds to (100) graphite planes . The wide diffraction peaks show that CSs have a low degree of crystallinity . Furthermore, the graphitic layer spacing for CSs derived from (002) peaks using the Bragg equation was around 0.36 nm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also the symmetrical nature of the GCD plots show good reversibility of electrochemical performance. 36 The C s values were calculated from the GCD curves in the current range of 1 to 10 A g À1 as depicted in Figure 4C. The C s value for 1 A g À1 of current density was obtained to be nearly 200 F g À1 while those values for current densities of 2, 3, 4, 5, 7, and 10 A g À1 are found to be 184, 174, 168, 160, 154, and 150 F g À1 , respectively.…”
Section: Electrochemical Performance Of Symmetric Devicementioning
confidence: 99%
“…The GCD diagrams as depicted in the Figure 4B exhibit linear shape in the charge‐discharge profiles indicating the EDLC type capacitive behaviour. Also the symmetrical nature of the GCD plots show good reversibility of electrochemical performance 36 . The C s values were calculated from the GCD curves in the current range of 1 to 10 A g −1 as depicted in Figure 4C.…”
Section: Electrochemical Analysismentioning
confidence: 99%